Elizabethkingia meningoseptica Carbapenem Resistance in Cerebrospinal Fluid Cultures of Patients Suspected of Bacterial Meningitis: A Case Report - Gita Setyanda, Yashinta Octavian (HM Publisher, 2024)
Background: Elizabethkingia meningoseptica is a Gram-negative bacterium that rarely causes meningitis in children. These infections are often resistant to carbapenem antibiotics, making diagnosis and treatment more complicated. Case presentation: A 1-month-old male patient was treated to the PICU of Dr. M. Djamil General Hospital Padang with symptoms of decreased consciousness, seizures, and fever. The patient was diagnosed with bacterial meningitis and was referred from Sungai Dareh Regional General Hospital with previous therapy for 4 days. A cerebrospinal fluid examination showed increased protein and decreased glucose, and a CT scan showed hydrocephalus. The cerebrospinal fluid culture showed growth of Elizabethkingia meningoseptica which was resistant to imipenem and meropenem. The patient was treated with a combination of non-carbapenem antibiotics and recovered from meningitis. Conclusion: Carbapenem-resistant Elizabethkingia meningoseptica is a rare causative agent of meningitis in children. Early diagnosis and treatment with appropriate non-carbapenem antibiotics are essential to increase the chance of cure.